2021
DOI: 10.1371/journal.pone.0244408
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study and pathway analysis identify NTRK2 as a novel candidate gene for litter size in sheep

Abstract: Litter size is one of the most important economic traits in sheep. Identification of gene variants that are associated with the prolificacy rate is an important step in breeding program success and profitability of the farm. So, to identify genetic mechanisms underlying the variation in litter size in Iranian Baluchi sheep, a two-step genome-wide association study (GWAS) was performed. GWAS was conducted using genotype data from 91 Baluchi sheep. Estimated breeding values (EBVs) for litter size calculated for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 77 publications
(54 reference statements)
3
14
0
Order By: Relevance
“…Given the different layers that make up the follicles and the need for communication and transfer material through these layers to the oocyte, the signi cance of these pathways seems logical. Identi ed pathways are frequently reported in previous studies (15,16,41,42).…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Given the different layers that make up the follicles and the need for communication and transfer material through these layers to the oocyte, the signi cance of these pathways seems logical. Identi ed pathways are frequently reported in previous studies (15,16,41,42).…”
Section: Discussionsupporting
confidence: 68%
“…PI3K-Akt signaling pathway has been identi ed in multiple publications associated with reproduction (15,42). Various normal cellular processes, such as cell proliferation, survival, motility, growth, cytoskeletal rearrangement, and metabolism, through multiple downstream targets, are regulated by the PI3K/PTEN/Akt pathway (43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The small number of available genotypes in this study can contribute to the low power of the association analysis, but the use of EBVs can increase the power to some extent as we have a better estimate of the actual genetic variance. EBVs can largely compensate for the limited number of genotypes to get reasonable estimates ( Abdoli et al, 2018 , 2019 ; Esmaeili-Fard et al, 2021 ). In this approach, first, we ran a pedigree-BLUP analysis using the classical repeatability animal model in the BLUPF90 software ( Masuda, 2019 ), and breeding values of all animals (genotyped and not genotyped animals) were estimated for all traits.…”
Section: Methodsmentioning
confidence: 99%
“…Understanding the molecular mechanism is essential for multiple births sheep breeding. Previous studies have shown that the prolificacy trait is quantitative and controlled by multiple genes ( Tang et al, 2019 ; Yang et al, 2019 ; Esmaeili-Fard et al, 2021 ). Identification of genes associated with reproduction is essential for sheep breeding.…”
Section: Introductionmentioning
confidence: 99%